ANALISIS PENDAPATAN USAHA PENGOLAHAN PELET KAYU MERANTI (Shorea leprosa Miq) DI KELURAHAN GAMBUT KECAMATAN GAMBUT KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Wasdiyanta; Minta Wahyuningsih, Yayuk; Zuraida; Ramadhana, Sri (Fakultas Pertanian UVAYA Banjarmasin, 2025)
The aim of this research is to determine technically and financially the meranti wood pellet processing business in Gambut Village, Gambut District, Banjar Regency by collecting primary and secondary data, taking respondents using the case study method. The results obtained are total variable costs of IDR 2,480,529, total revenue obtained from the sale of all Meranti Wood Pellet products is IDR 4,965,000 and Revenue is IDR 2,484,471.